Research Policies in Science and Technology in Educational Settings: International Paradigms. Period 2013-2023 - Gómez Velasco, Nubia Yaneth; Ochoa Rodríguez, Yon Jairo; Sánchez García, Santos Morena; Manrique Rodríguez, Ángela María (Revista Historia de la Educación Latinoamericana, 2024)
Objective: The aim of this study is to examine the policies and tensions between the OECD and UNESCO over the past ten years. We focus on their impact on Higher Education Institutions. Originality/contribution: The importance of this study lies in the notable influence these organizations exert on university policies through specific guidelines, as well as in the relevance and scarcity of resources allocated to research in science and technology in the educational sphere. Method/Data Collection Strategies: The study employs a mixed methodological approach, blending quantitative and qualitative research. Document review and analysis of science and technology indicators were used as primary strategies to gather and analyze data. Through this approach, trends and discrepancies in the research policies of both organizations could be identified and evaluated. Conclusion: The results highlight a trend of uniformity in OECD policies on science, technology, and innovation (STI), often overlooking specific contexts, investment gaps and human capital in different regions. On the other hand, tensions are identified with UNESCO in key areas such as research priorities, equity in open access, ethics and social responsibility. In conclusion, the study provides recommendations to strengthen research and innovation in universities, emphasizing the need to consider local contexts and promote more inclusive and equitable policies. This study contributes to understanding university policies and serves as a reference for future research in the field of institutional research policies.